dwt 2018
DOI: 10.5004/dwt.2018.22119
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on productivity intensification of HDH desalination unit utilizing two-stage dehumidification

Abstract: a b s t r a c tIn this study, an experimental investigation is performed on a two-stage dehumidification water desalination system utilizing a humidification-dehumidification process that has been accomplished using heat pump. The air is heated by means of heat pump condenser to increase its ability to efficiently humidify, while condensation takes place at the heat pump evaporator section. Additionally, in order to enhance the dehumidification efficiency a per-dehumidification process was performed to the hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The proposed theoretical model is related to the spraying atomization method, which was already validated by our previous work [19]. The main results are shown in Figure 6, in terms of the productivity of the desalination unit.…”
Section: Resultsmentioning
confidence: 64%
See 4 more Smart Citations
“…The proposed theoretical model is related to the spraying atomization method, which was already validated by our previous work [19]. The main results are shown in Figure 6, in terms of the productivity of the desalination unit.…”
Section: Resultsmentioning
confidence: 64%
“…In the humidification process, the flow of spraying saline water is in parallel with the airflow according to our previous results (El-Maghlany et al [19]), which indicated that the highest humidification effectiveness and productivity were obtained with the parallel spraying system. Therefore, the model of the humidification process is based on a parallel-flow heat exchange between the sprayed saline water and the airflow.…”
Section: Humidifiermentioning
confidence: 69%
See 3 more Smart Citations